2012
DOI: 10.1001/jama.2011.2029
|View full text |Cite
|
Sign up to set email alerts
|

Symptomatic In-Hospital Deep Vein Thrombosis and Pulmonary Embolism Following Hip and Knee Arthroplasty Among Patients Receiving Recommended Prophylaxis

Abstract: Using current VTE prophylaxis, approximately 1 in 100 patients undergoing TPKA and approximately 1 in 200 patients undergoing TPHA develops symptomatic VTE prior to hospital discharge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
92
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 240 publications
(104 citation statements)
references
References 76 publications
5
92
1
1
Order By: Relevance
“…The diagnosis of VTE was based on clinical suspicion and confirmed with imaging studies, such as Doppler sonography and chest computer tomography. While a recent systematic review reported a much lower incidence of VTE (0.5% knee to 1% hip TJA) among patients receiving recommended prophylaxis, data capture in previous studies was limited to the inpatient period only, highlighting the importance of ongoing active surveillance after discharge (18). Furthermore, the rate of VTE was higher in patients undergoing knee TJA compared to hip TJA.…”
Section: Discussionmentioning
confidence: 97%
“…The diagnosis of VTE was based on clinical suspicion and confirmed with imaging studies, such as Doppler sonography and chest computer tomography. While a recent systematic review reported a much lower incidence of VTE (0.5% knee to 1% hip TJA) among patients receiving recommended prophylaxis, data capture in previous studies was limited to the inpatient period only, highlighting the importance of ongoing active surveillance after discharge (18). Furthermore, the rate of VTE was higher in patients undergoing knee TJA compared to hip TJA.…”
Section: Discussionmentioning
confidence: 97%
“…Although venous thromboembolic (VTE) disease has been researched extensively and discussed in hip and knee arthroplasties [6,8,10], the phenomenon has not been as well described after shoulder surgery. Deep vein thrombosis (DVT) and pulmonary embolism (PE) are potential complications of shoulder procedures such as arthroscopy and closed reductions of the shoulder [2,11,14].…”
Section: Introductionmentioning
confidence: 99%
“…Median Age (yrs) 71 72 *f/u=follow up major guidelines, (study sample sizes ranging from 4177 to 5738) [16][17][18]. Our findings of both symptomatic and asymptomatic DVT and PE (fatal and non-fatal) amongst post operative TKR patients receiving short course anti-coagulation therapy lie well within these indices.…”
Section: -91 54-91mentioning
confidence: 58%